If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -6x = -90x + 40 Reorder the terms: 40 + -6x = 40 + -90x Add '-40' to each side of the equation. 40 + -40 + -6x = 40 + -40 + -90x Combine like terms: 40 + -40 = 0 0 + -6x = 40 + -40 + -90x -6x = 40 + -40 + -90x Combine like terms: 40 + -40 = 0 -6x = 0 + -90x -6x = -90x Solving -6x = -90x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '90x' to each side of the equation. -6x + 90x = -90x + 90x Combine like terms: -6x + 90x = 84x 84x = -90x + 90x Combine like terms: -90x + 90x = 0 84x = 0 Divide each side by '84'. x = 0 Simplifying x = 0
| -53=n+7 | | X^2+2xy=-8 | | 9(4-6)+55= | | -15.00-2.00x=25.00 | | f(x)=5x^2+10x+3 | | -15.00-12.00x=25.00 | | 5.75=3/4x | | -7(r-9)= | | 5(2x+3)=4x-9 | | 6r+5(4r-12)= | | 7+7x=2x+32 | | 85=m-4 | | 43+10n=24n-27 | | (x-4y)dx+(x+2y)dy=0 | | 4.8/2 | | 2.5/465 | | 7(5n+9)+n= | | h(t)=27 | | Log(8)+log(-5x)=1 | | -5m+45=27-7m | | 7x-10=6(11-3x) | | 4x-11=9x-26 | | 18-3=15 | | 5=x-10y | | 4/3.14=70 | | 4x+3(7x-11)=192 | | 12x+18(1911-x)=31752 | | sin(x)-2=0 | | ln(y)=0.42 | | 18z=234 | | 18z=18 | | sin^2(3x)-2sin(3x)+1=0 |